2008
DOI: 10.1016/j.biochi.2008.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of the human DNA repair protein metnase influence lentiviral genomic integration

Abstract: We recently identified a Transposase domain protein called Metnase, which assists in repairing DNA double-strand breaks (DSB) via non-homologous end-joining (NHEJ), and is important for foreign DNA integration into a host cell genome. Since integration is essential for productive lentiviral infection we examined whether Metnase expression levels could have an influence on lentiviral genomic integration. Using cells stably transduced to either over-or under-express Metnase we determined that the expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…However, given that DNA end joining often requires processing of non-compatible ends additional factors are necessary for completion of NHEJ in a cell-free system (22, 28, 29). We previously reported that Metnase forms DSB foci with other repair factors and stimulates DSB repair and genomic integration of foreign DNA in vivo (32, 39, 44, 59). In this study, we showed that Metnase possesses a unique endonuclease activity that plays a positive role in the joining of non-compatible ends in cell-free system.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that DNA end joining often requires processing of non-compatible ends additional factors are necessary for completion of NHEJ in a cell-free system (22, 28, 29). We previously reported that Metnase forms DSB foci with other repair factors and stimulates DSB repair and genomic integration of foreign DNA in vivo (32, 39, 44, 59). In this study, we showed that Metnase possesses a unique endonuclease activity that plays a positive role in the joining of non-compatible ends in cell-free system.…”
Section: Discussionmentioning
confidence: 99%
“…Metnase levels were assessed using reverse-transcribed polymerase chain reaction (RT-PCR) and Western blotting as we described. 12,22 Each experiment using shRNA repressed Metnase was performed in at least 2 independent clones, with nearly identical results.…”
Section: Manipulating Metnase Levelsmentioning
confidence: 99%
“…Other cellular repair factors have been demonstrated to suppress viral infection, including XPB and XPD [86] of the nucleotide excision repair pathway, RAD52 [87], and Rad18 [88]. Metnase is a protein that promotes DSB repair by NHEJ [89] and has been suggested to influence lentivirus integration [90]. Defective repair pathways might indirectly affect virus integration by providing longer lasting breaks that are exploited by viral genomes.…”
Section: Dna Damage Signaling In Viral Infectionmentioning
confidence: 99%